2022
DOI: 10.1097/sap.0000000000003069
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Role of Subsequent Thrombocytopenia in Necrotizing Fasciitis Without Liver Disease

Abstract: Background: Necrotizing fasciitis (NF) is a life-threatening disease with a fulminant presentation. Although early diagnosis can be aided by combining physical examination, the Laboratory Risk Indicator for Necrotizing Fasciitis score, and computed tomography, a mortality rate of 30% is still reported. In the modern times, an economical and efficient biomarker for predicting mortality in NF patients is still lacking. Platelet count is typically measured in routine blood tests and aids in predicting disease sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…Therefore, platelet counts have a bimodal relationship with outcomes, in which both abnormally high as well as abnormally low platelet counts are associated with adverse outcomes following infection 3,19,20 . In the present study, we observed that non-survivors had lower platelet counts and greater proportion of patients had thrombocytopenia at admission compared with survivors, aligning with recent findings by Chen et al 21 .…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, platelet counts have a bimodal relationship with outcomes, in which both abnormally high as well as abnormally low platelet counts are associated with adverse outcomes following infection 3,19,20 . In the present study, we observed that non-survivors had lower platelet counts and greater proportion of patients had thrombocytopenia at admission compared with survivors, aligning with recent findings by Chen et al 21 .…”
Section: Discussionsupporting
confidence: 93%
“…The contribution of coagulation dysfunction to the negative impact on mortality in necrotizing soft tissue infections is well established, with declining platelet counts indicating severity in critically ill patients, and coagulopathy correlating with high mortality rates (21,22). Bleeding or disseminated intravascular coagulation events from coagulopathy complicate the treatment of critically ill patients and adversely affect their clinical outcomes (23,24).…”
Section: ) Predictive Factors For In-hospital Mortalitymentioning
confidence: 99%